2011
DOI: 10.1007/s11145-010-9276-5
|View full text |Cite
|
Sign up to set email alerts
|

Children’s morphological awareness and reading ability

Abstract: We investigated the effects of morphological awareness on five measures of reading in 103 children from Grades 1 to 3. Morphological awareness was assessed with a word analogy task that included a wide range of morphological transformations. Results indicated that the new measure had satisfactory reliability, and that morphological awareness was a significant predictor of word reading accuracy and speed, pseudoword reading accuracy, text reading speed, and reading comprehension, after controlling the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
310
2
39

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(403 citation statements)
references
References 32 publications
29
310
2
39
Order By: Relevance
“…The results of this study are unique as they provide evidence of one possible directional path where reading skill can be seen as influencing later MA whereas past correlational and longitudinal research has demonstrated the opposite situation where MA has been found to predict later reading achievement (Carlisle, 2000;Deacon & Kirby, 2004;Kirby et al, 2012;Roman et al, 2009). Taken together, the findings of this study offers support for the bi-directional relationship between word reading skills and MA as proposed by Deacon, Benere, and Pasquarella (2013).…”
Section: Do We See a Significant Change In Ma From Kindergarten To Grsupporting
confidence: 60%
See 1 more Smart Citation
“…The results of this study are unique as they provide evidence of one possible directional path where reading skill can be seen as influencing later MA whereas past correlational and longitudinal research has demonstrated the opposite situation where MA has been found to predict later reading achievement (Carlisle, 2000;Deacon & Kirby, 2004;Kirby et al, 2012;Roman et al, 2009). Taken together, the findings of this study offers support for the bi-directional relationship between word reading skills and MA as proposed by Deacon, Benere, and Pasquarella (2013).…”
Section: Do We See a Significant Change In Ma From Kindergarten To Grsupporting
confidence: 60%
“…Studies have demonstrated that an awareness of morphemes, the smallest linguistic units retaining meaning, contributes to word recognition, spelling, and reading comprehension, independent of orthographic processing, phonological awareness, RAN, and vocabulary (Carlisle, 2000;Casalis & Louis-Alexandre, 2000;Deacon & Kirby, 2004;Kirby et al, 2012;Roman, Kirby, Parrila, Wade-Woolley, & Deacon, 2009). …”
Section: Morphological Awarenessmentioning
confidence: 99%
“…By analyzing the results of each article included in the review, positive correlations can be observed between morphological awareness tests and reading and writing skills. Furthermore, a relationship between morphological awareness and the speed of reading and word identification was observed (19) . Taking the relevant limitations into account, most of the studies consider, respectively, the need for tests with greater validity and reliability for the assessment of morphological awareness (22,26) , as well as the need for inclusion of tests for later control of phonological awareness, vocabulary, and general knowledge, thus reducing the increase of influences and confounding factors (12,18,21,24,31) .…”
Section: Resultsmentioning
confidence: 97%
“…There was a predominance of grammatical analogy tests, morphological decision, and creation of neologisms for assessment of morphological awareness; and testing of receptive vocabulary with pictures and WISC III digit span tests for assessment of vocabulary (19,21,23,25,26) . The predominant use of tests of grammatical analogy, morphological decision, and creation of neologisms to evaluate morphological awareness corroborates recent studies in Brazilian Portuguese (9,21) that have tested such evidence through appropriate statistical analysis and concluded that they present greater evidence of validity to assess the morphological awareness skill, however with differentiated levels of correlation for each school grade and component assessed (derivational or inflectional morphology).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation